2012
DOI: 10.1111/j.1365-2915.2012.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Carrion flies of forensic interest: a study of seasonal community composition and succession in Lisbon, Portugal

Abstract: Information on Diptera community, seasonality and successional patterns in every geographical region is fundamental for the use of flies as forensic indicators of time of death. In order to obtain these data from the Lisbon area (Portugal), experiments were conducted during the four seasons of the year, using piglet carcasses as animal models. Five stages were recognized during the decomposition process. The stages, besides visually defined, could be separated taking into account the occurrence and abundance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 25 publications
8
38
1
2
Order By: Relevance
“…The occurrence of carrion flies was clearly influenced by temperature effects, as expected from the literature (Tantawi et al 1996;Martínez-Sánchez et al 2000;Schrӧeder et al 2003;Arnaldos et al 2004;Grassberger and Frank 2004;Hwang and Turner 2005;Anton et al 2011;Battán Horenstein and Salvo 2012;Prado e Castro et al 2012;George et al 2013). The highest number of specimens and species was caught with a high average air temperature, while the lowest values were obtained in low temperatures, which is in agreement with the results obtained from western Spain by Martínez-Sánchez et al (2000).…”
Section: Temperature Effects On Species Abundance and Richnesssupporting
confidence: 91%
See 3 more Smart Citations
“…The occurrence of carrion flies was clearly influenced by temperature effects, as expected from the literature (Tantawi et al 1996;Martínez-Sánchez et al 2000;Schrӧeder et al 2003;Arnaldos et al 2004;Grassberger and Frank 2004;Hwang and Turner 2005;Anton et al 2011;Battán Horenstein and Salvo 2012;Prado e Castro et al 2012;George et al 2013). The highest number of specimens and species was caught with a high average air temperature, while the lowest values were obtained in low temperatures, which is in agreement with the results obtained from western Spain by Martínez-Sánchez et al (2000).…”
Section: Temperature Effects On Species Abundance and Richnesssupporting
confidence: 91%
“…Conversely, most of the Diptera species from family Muscidae documented on the first seven days in carcasses in Salamanca (Martínez-Sánchez et al 2000) were not part of the insect fauna of our study. Although, the study performed in Murcia (Arnaldos et al 2004) and the one performed in Lisbon (Prado e Castro et al 2012) found the same species of muscid flies as the ones found in this study, except for the species H. dentipes was collected in Prado e Castro et al 2012 but not here, and a trade in the genera Phaonia, as the present study collected the species Phaonia trimaculata and Prado e Castro et al collected P. subventa (Table 6). These results suggest that forensically important Muscidae communities are more region-specific and/or more bait sensitive than Calliphoridae.…”
Section: Small Bait Traps As An Efficient Alternative To Capture Firssupporting
confidence: 46%
See 2 more Smart Citations
“…[17]. A similar distribution pattern has been described in Lisbon in Portugal although somewhat fewer M. stabulans were recorded in summer than in the spring and autumn [18]. Skidmore (1985) [11] [21] although some authors state that state that they usually overwinter as pupae [22].…”
Section: Influence Of Alternative Baits On Oviposition and Larval Devmentioning
confidence: 62%